A heterologous prime-boost strategy for immunization against Dengue virus combining the Tetra DIIIC subunit vaccine candidate with the TV005 live-attenuated tetravalent vaccine. (15th May 2019) - Valdés, Iris; Izquierdo, Alienys; Cobas, Karem; Thao, Phuong; Anh Duc, Hoang; Duc Loc, Hoang; Dung, Le Trung; Lazo, Laura; Suzarte, Edith; Pérez, Yusleidi; Romero, Yaremis; Yaugel, Melyssa; et al.
Abstract : The development of live-attenuated vaccines against Dengue virus (DENV) has been problematic. Dengvaxia, licensed in several countries where DENV is endemic, has shown low efficacy profiles and there are safety concerns prohibiting its administration to children younger than 9 years old, and the live-attenuated tetravalent vaccine (LATV) developed by NIAID has proven too reactogenic during clinical trialing. In this work we examined whether the combination of TV005, a LATV-derived formulation, with Tetra DIIIC, a subunit vaccine candidate based on fusion proteins derived from structural proteins from all four DENV serotypes, can overcome the respective limitations of these two vaccine approaches. Rhesus macaques were first primed with one or two doses of Tetra DIIIC and then boosted with TV005, following the time course of the appearance of virus-binding and neutralizing antibodies, and evaluating protection by means of a challenge experiment with wild-type viruses. Although the two evaluated prime-boost regimes were equivalent to a single administration of TV005 in terms of the development of virus-binding and neutralizing antibodies as well as the protection against viral challenge, both regimes reduced vaccine viremia to undetectable levels. Thus, the combination of Tetra DIIIC with TV005 offers a potential solution to the reactogenicity problems, which have beset the development of the latter vaccine candidate.